1996
DOI: 10.1177/027836499601500405
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Sensing of Known Planar Shapes

Abstract: Industrial assembly involves sensing the pose (orientation and position) of a part. Efficient and reliable sensing strategies can be developed for an assembly task if the shape of the part is known in advance. In this article we investigate two problems of determining the pose of a polygonal part of known shape for the cases of a continuum and a finite number of possible poses respectively.The first problem, named sensing by inscription, involves determining the pose of a convex n-gon from a set of m supportin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 51 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…That motivation is rooted in a long line of work on motion planning with uncertainty from the 1980s and 1990s [9,59,60,22,10,14,12,72,15,16,53,33,55,11] as well as related work on understanding information invariants, such as natural tradeoffs between sensing and action [70,21,18,2,19,52,26,17,45,46]. The tools for characterizing system capabilities discussed in Sections 9 and 10 provide a concise topological language for making such comparisons.…”
Section: An Underlying Motivationmentioning
confidence: 99%
“…That motivation is rooted in a long line of work on motion planning with uncertainty from the 1980s and 1990s [9,59,60,22,10,14,12,72,15,16,53,33,55,11] as well as related work on understanding information invariants, such as natural tradeoffs between sensing and action [70,21,18,2,19,52,26,17,45,46]. The tools for characterizing system capabilities discussed in Sections 9 and 10 provide a concise topological language for making such comparisons.…”
Section: An Underlying Motivationmentioning
confidence: 99%
“…Timothy argues that a piecework can be covered by a known object like a mask during an assembly process [30]. Jia and Erdmann in [19] introduce a technique by which the pose of polygonal parts can be determined by acquiring data from two views. In [6,11,24] registration marks are placed on the parts to recognize and localize an object pose.…”
Section: Related Workmentioning
confidence: 99%
“…In our previous work [29], we introduced the methods of cone inscription and point sampling that compute the poses of known shapes from a continuum and a finite number of possibilities, respectively, using simple geometric constraints such as coincidence and containment. Paulos and Canny [41] studied the problem of finding optimal point probes for refining the pose of a polygonal part with known geometry from an approximate pose; they revealed that this problem is dual to the grasping problem of computing optimal finger placements and gave an efficient near-optimal solution.…”
Section: Roboticsmentioning
confidence: 99%
“…Hence we choose to evaluate dL 2 f ω numerically. Solve equation (29) under n = 4 and take the inverse of the solution:…”
Section: A Gauthier-hammouri-othman Observermentioning
confidence: 99%